The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.14393/bj-v32n1a2016-26270
|View full text |Cite
|
Sign up to set email alerts
|

Seedling production of Jatropha curcas in substrates fertilized with lithothamnium

Abstract: ABSTRACT:Seedlings of high quality are essential for the deployment of homogeneous plants. Thus, was evaluated the formation of seedlings of Jatropha (Jatropha curcas L.) in different substrates fertilized with fertilizer-based lithothamnium. It was used substrates I) mixed of: never cultivated soil, cattle manure and sand in proportions: 3:1:1 volume/volume (v/v); II) commercial substrate Tropstrato ® ; III) cattle manure and carbonized rice straw in proportions: 1:1 (v/v); IV) birds manure, carbonized ric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 6 publications
(6 reference statements)
0
4
0
3
Order By: Relevance
“…Results in this phase are similar to those found by Oliveira et al (2014), where the authors found 17 corms per lineal meter in irrigated sugarcane and without water restriction for the same cultivar. This behavior is probably due to water availability and the effect of lithothanmium, since it potentiates potassium uptake, intensifying the appearance of number of corms per linear meter (Evangelista, Evangelista, Vieira & Júnior, 2016). The positive effect of lithothanmium application can be attributed to the presence of neutral calcium with formation of chelates contributing to greater plant uptake (Evangelista et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results in this phase are similar to those found by Oliveira et al (2014), where the authors found 17 corms per lineal meter in irrigated sugarcane and without water restriction for the same cultivar. This behavior is probably due to water availability and the effect of lithothanmium, since it potentiates potassium uptake, intensifying the appearance of number of corms per linear meter (Evangelista, Evangelista, Vieira & Júnior, 2016). The positive effect of lithothanmium application can be attributed to the presence of neutral calcium with formation of chelates contributing to greater plant uptake (Evangelista et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, reduction in corm diameter probably occurs due to reduction in number of plants as a consequence of high population competition in this phase. As for the influence of lithothanmium it could have been damaged because it is a rapid release product and causes depressive effect in plants, especially in soils with base saturations above 70%; this is because it increases soil pH and inhibits nutrient uptake (Evangelista et al, 2016). Maximum LAI (1.91 m 2 .m -2 ) in Phase I ( Figure 4A) Figure 4B).…”
Section: Discussionmentioning
confidence: 99%
“…Neste trabalho a vermiculita apresentou o maior resultado absoluto, porém estatisticamente não podemos afirmar ser este substrato melhor que os outros substratos testados. O Lithothamnium tem demonstrado potencial no uso como bioestimulante na produção de mudas no Brasil e os estudos realizados comprovam sua viabilidade para mudas de pinhão manso (EVANGELISTA et al, 2016), café arábica (RODRIGUEZ et al, 2017) e maracujazeiro doce (SOUZA et al, 2007). Na produção de mudas do mamoeiro tem sido verificado efeito dependendo da dose e do genótipo avaliado, variando entre 2 e 3 kg/m³ com resultados variáveis no desenvolvimento da parte aérea e do sistema radicular (TEIXEIRA et al, 2009;HAFLE et al, 2009).…”
Section: Página | 602unclassified
“…Além de uma irrigação bem manejada, o fornecimento de nutrientes para a planta torna-se prática fundamental. Neste contexto, o sistema de produção orgânico além de nutrir as plantas, contribui para preservação do meio ambiente e agrega valor ao produto colhido (EVANGELISTA et al, 2016). O principal produto da cana orgânica é o açúcar orgânico, enquanto outros produtos vêm se destacando, entre eles o melado e a aguardente.…”
Section: Introductionunclassified
“…Quanto à influência do lithothamnium, segundo Evangelista et al (2016), solos com saturações por bases acima de 70%, juntamente, com um fertilizante de rápida liberação como o lithothamnium causa efeito depressivo nas plantas quando fornecido em altas doses, pelo aumento do pH do solo, reduzindo a absorção de nutrientes pela planta.…”
unclassified